Paradigma Lingkungan Guru - Risa Bernadip Umar (Universitas Negeri Jakarta, 2016)
The purpose of this study was to gain an overview of the relationship between the naturalist intelligence, locus of control, and knowledge of the ecosystem with environmental paradigm. The paradigm of the teacher on the environment need to be held for teachers when teaching subjects need to be practiced in high school biology. This study used a survey method, the sample in this study were 95 teachers drawn at random. Data were collected through participant observation using the instrument in the form of questions and statements. Analysis and interpretation of the data showed that (1) There is a positive relationship between the level of naturalist intelligence with environmental paradigm. (2) There is a positive relationship between locus of control with environmental paradigm. (3) There is a positive relationship between knowledge of ecosystems to environmental paradigm. (4) There is a positive relationship between the naturalist intelligence, locus of control and knowledge of the ecosystem, together with environmental paradigm. The findings of this study concluded that with the increase naturalist intelligence, locus of control and knowledge of ecosystem biology teacher collaboration will improve also new environmental paradigm.